Eukaryotic Voltage-Gated Sodium Channels: On Their Origins, Asymmetries, Losses, Diversification and Adaptations - Fux, Julia E.; Mehta, Amrit; Moffat, Jack; Spafford, J. David (Frontiers in Physiology, 2018)
The appearance of voltage-gated, sodium-selective channels with rapid gating kinetics was a limiting factor in the evolution of nervous systems. Two rounds of domain duplications generated a common 24 transmembrane segment (4 × 6 TM) template that is shared amongst voltage-gated sodium (Nav1 and Nav2) and calcium channels (Cav1, Cav2, and Cav3) and leak channel (NALCN) plus homologs from yeast, different single-cell protists (heterokont and unikont) and algae (green and brown). A shared architecture in 4 × 6 TM channels include an asymmetrical arrangement of extended extracellular L5/L6 turrets containing a 4-0-2-2 pattern of cysteines, glycosylated residues, a universally short III-IV cytoplasmic linker and often a recognizable, C-terminal PDZ binding motif. Six intron splice junctions are conserved in the first domain, including a rare U12-type of the minor spliceosome provides support for a shared heritage for sodium and calcium channels, and a separate lineage for NALCN. The asymmetrically arranged pores of 4x6 TM channels allows for a changeable ion selectivity by means of a single lysine residue change in the high field strength site of the ion selectivity filter in Domains II or III. Multicellularity and the appearance of systems was an impetus for Nav1 channels to adapt to sodium ion selectivity and fast ion gating. A non-selective, and slowly gating Nav2 channel homolog in single cell eukaryotes, predate the diversification of Nav1 channels from a basal homolog in a common ancestor to extant cnidarians to the nine vertebrate Nav1.x channel genes plus Nax. A close kinship between Nav2 and Nav1 homologs is evident in the sharing of most (twenty) intron splice junctions. Different metazoan groups have lost their Nav1 channel genes altogether, while vertebrates rapidly expanded their gene numbers. The expansion in vertebrate Nav1 channel genes fills unique functional niches and generates overlapping properties contributing to redundancies. Specific nervous system adaptations include cytoplasmic linkers with phosphorylation sites and tethered elements to protein assemblies in First Initial Segments and nodes of Ranvier. Analogous accessory beta subunit appeared alongside Nav1 channels within different animal sub-phyla. Nav1 channels contribute to pace-making as persistent or resurgent currents, the former which is widespread across animals, while the latter is a likely vertebrate adaptation.